2014
DOI: 10.1038/ncomms5880
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic antibody-linked nanomatchmakers for therapeutic cell targeting

Abstract: Stem cell transplantation is a promising strategy for therapeutic cardiac regeneration, but current therapies are limited by inefficient interaction between potentially beneficial cells (either exogenously transplanted or endogenously recruited) and the injured tissue. Here we apply targeted nanomedicine to achieve in vivo cell-mediated tissue repair, imaging and localized enrichment without cellular transplantation. Iron nanoparticles are conjugated with two types of antibodies (one against antigens on therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
113
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 33 publications
1
113
0
1
Order By: Relevance
“…In addition to the stem cell tracking, SPIONs have also been used to magnetically target stem cells to lesion sites, as described by Nishida et al 77 Hamasaki et al, 78 successfully showed, in organotypic cultures, the possibility of enhancing axon formation by magnetically localizing SPION-labeled cells. Studies on the use of SPIONs to focus the delivery of stem cells to specific areas are still being conducted, and have been published by Cheng et al 79 …”
Section: Tracking Stem Cells With Superparamagnetic Iron Oxide Nanopamentioning
confidence: 99%
“…In addition to the stem cell tracking, SPIONs have also been used to magnetically target stem cells to lesion sites, as described by Nishida et al 77 Hamasaki et al, 78 successfully showed, in organotypic cultures, the possibility of enhancing axon formation by magnetically localizing SPION-labeled cells. Studies on the use of SPIONs to focus the delivery of stem cells to specific areas are still being conducted, and have been published by Cheng et al 79 …”
Section: Tracking Stem Cells With Superparamagnetic Iron Oxide Nanopamentioning
confidence: 99%
“…10 Moreover, concurrent or subsequent MRI can be used for noninvasive monitoring of drug distribution and successful delivery to the desired organ in vivo. 11 This review is in line with recent publications on MDT, 9,12,13 but in addition to illustrating the basic conceptual and biophysical principles, we particularly focus on new research activities and achievements in the cardiovascular field, mainly in the management of AMI. Based on the presentation of successful MDT applications in preclinical models of AMI, novel approaches and the translational potential of MDT are discussed.…”
Section: Introductionmentioning
confidence: 67%
“…The complex was prepared for IV injection and tested in a rodent model of ischemia/ reperfusion. 11 In order to enrich these "matchmakers" at the infarcted tissue, in the first place, a 1.3 T magnet was placed over the left thoracic region for 10 minutes after the onset of reperfusion. In T2*-weighted MR images acquired 24 hours later, relative hypoenhancement in the left ventricular anterior wall was significantly higher in the magnet-positive group as compared to controls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic fields can be generated by implanted or external devices to safely direct the movement of magnetically-labeled cells within the body 8 . Numerous research efforts have focused on magnetically directed targeting of stem cells to injured tissues such as the heart [9][10][11][12][13][14] , retina 15 , lung 16 , skin 17 , spinal cord 18,19 , bone 20 , liver 21 , and muscle 22,23 in order to improve regeneration outcomes.…”
Section: Introductionmentioning
confidence: 99%